Lienminh Chicken Breed: Native Breed and Livelihood of People on District-Island Cat Hai of Hai Phong City, Vietnam - Doan, Bui Huu; Dang, Pham Kim; Tuan, Hoang Anh; Thinh, Nguyen Hoang (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
In Vietnam, besides the exotic breeds, native chicken is not only more and more playsimportant role in household economy, but also perform other functions, in support of the cultural,social in the last years and in special in the context globalization in recent future of developingcountry. The characterization and evaluation of the role of native chicken as Lienminh breed inlivehoods of Vietnamese is necessary for the strategy of conservation and use the native chickengenetic. In order to determine the general information related the status and economic efficiency ofLienminh chickens production. A cross-sectional study was conducted on 30 households who raisingLienminh chicken in Cathai Island  by using semi-structured questionnaire. For morpho-biometriccharacteristics was identify in 200 adult chickens according to FAO standards. For economictechnical parameters was determined on 100 broiler chickens (50 males and 50 females) fromhatching to 16 weeks in the hothouse in the same local. The research results show that, about 54%Lienminh breed present in the chicken population in Cathai district, most of them are raised inbackyard. The farmer fed average about 30g of feed/day/ chicken. Lienminh breed washaateized  olos, ost of the oostes feathes % ee eddish-brown, and light yellowfo the feale. At the adults age, the ea eight of ale ad female were, respectively, 4,0 – 4,3kg and 3.2 to 3.4 kg. The yield of carcass, thigh and breast meat are respectively, about 70.53 ± 3.86%, 18.24 ± 1.15 %; and 17.06 ± 1.09 %. The meat quality was especially excellent (evaluate byconsumer local) and the price was 2.5 – 3,0 times higher than that of other exotic chicken breeds.The age at the first egg are at 28 weeks; with body weight of about 2.25kg. Mean of Yearly eggnumbers were 75.6±6.6 eggs. The rate of hatching eggs were 85.55±9.32%. The economic efficiencyof Lienminh chicken production is higher than others exotic breed, it will increase the incomesignificantly and contribute to poverty reduction for local people.Key Word: Native Chicken, Morpho-Biometric, Lienminh Chicken Breed, Vietnam